THE MANIFESTATION OF SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF COPING BEHAVIOR STRATEGIES AMONG STUDENT YOUTH (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the relationship between the psychological views of foreign psychologists in this regard, draws conclusions based on the results of research conducted in the field of protective mechanisms for student youth in extreme situations and the manifestation of coping behavior.